2015
DOI: 10.1134/s0006350915010170
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic nature of erythrocyte hemolysis induced by low doses of ionizing radiation

Abstract: It is shown that exposure of rat erythrocytes to low doses of ionizing radiation (0.04, 0.08, 0.16, 0.25, and 0.33 mGy) leads to nonlinear changes in lipid peroxidation processes in the membrane of erythro cytes, their electrophoretic mobility, and osmotic resistance. Ionizing radiation in the dose range from 0.08 to 0.16 mGy apparently triggers apoptosis, leading to deceleration of hemolysis and stabilization of erythro cytes, which was confirmed by morphological changes in erythrocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…There is other research that also studied the effects of low-dose ionizing radiation on RBC damage. Krylov et al 2015 showed that β-ionizing radiation ( 90 Sr-90 Y source) in the dose range from 0.08 to 0.16 mGy contributed to the deceleration of hemolysis and the stabilization of rat red blood cells 35 of hemolysis could be distinguished in five and three characteristic periods for RBCs isolated from healthy people and people with diabetes, respectively 36 .It is obvious that there are several factors contributing to the RBC response to ionizing radiation:the type of radiation (β-, γ-, X-rays), the radiation dose, and the characteristics of the cells (animal or human cells, normal or abnormal cells). Therefore, our in vitro data using hemolysis as the biological endpoint suggested that the medical diagnostic low-dose X-rays (energy of 80 kVp) did not induce harmful effects on human RBCs.…”
Section: Discussionmentioning
confidence: 99%
“…There is other research that also studied the effects of low-dose ionizing radiation on RBC damage. Krylov et al 2015 showed that β-ionizing radiation ( 90 Sr-90 Y source) in the dose range from 0.08 to 0.16 mGy contributed to the deceleration of hemolysis and the stabilization of rat red blood cells 35 of hemolysis could be distinguished in five and three characteristic periods for RBCs isolated from healthy people and people with diabetes, respectively 36 .It is obvious that there are several factors contributing to the RBC response to ionizing radiation:the type of radiation (β-, γ-, X-rays), the radiation dose, and the characteristics of the cells (animal or human cells, normal or abnormal cells). Therefore, our in vitro data using hemolysis as the biological endpoint suggested that the medical diagnostic low-dose X-rays (energy of 80 kVp) did not induce harmful effects on human RBCs.…”
Section: Discussionmentioning
confidence: 99%
“…MDA concentration was assessed by the formation of colored trimethine complex with absorption maximum at 532 nm [6]. The molar extinction coefficient E=1.56•10 -5 М -1 •cm -1 was used to calculate concentration.…”
Section: Methodsmentioning
confidence: 99%